Use of gonadotropin-releasing hormone agonists in transgender and gender diverse youth: a systematic review - Tornese, Gianluca; Di Mase, Raffaella; Munarin, Jessica; Ciancia, Silvia; Santamaria, Fabiana; Fava, Daniela; Candela, Egidio; Capalbo, Donatella; Ungaro, Carla; Improda, Nicola; Diana, Pierluigi; Matarazzo, Patrizia; et al. (Frontiers in Endocrinology, 2025)
IntroductionPuberty suppression using gonadotropin-releasing hormone agonists (GnRHa) is a reversible medical intervention that halts endogenous puberty, allowing transgender and gender-diverse (TGD) adolescents to avoid the development of secondary sexual characteristics that may cause psychological distress. This pause in pubertal progression provides time to explore gender identity or facilitates alignment with affirmed gender in those with an established identity. While widely used, long-term evidence on the efficacy and safety of GnRHa in this population remains limited. This systematic review aims to synthesize current data on the benefits and potential risks of GnRHa in TGD adolescents.MethodsWe conducted a comprehensive literature search across PubMed, EMBASE, Cochrane Library, and other databases, covering studies published from February 2011 to February 2024. Eligible studies included adolescents under 18 with gender dysphoria or incongruence treated with GnRHa, reporting outcomes related to efficacy or side effects. Fifty-one studies met inclusion criteria, and data on physical health, mental health, bone density, fertility, and adverse events were extracted and assessed using the GRADE approach.ResultsOf the 51 studies, 22 were rated as moderate to high-quality evidence. GnRHa effectively suppressed puberty and secondary sex characteristics. Effects on growth and body composition varied; bone mineral density declined during treatment, particularly in AMAB individuals. Mental health improved significantly, including reduced depression, anxiety, and suicidality—especially when GnRHa was followed by gender-affirming hormone therapy (GAHT). Quality of life improved over time, while body dissatisfaction often persisted during suppression and improved after GAHT or surgery. No moderate- or high-quality evidence was found on fertility, sexual function, or cancer risk.ConclusionGnRHa is effective in halting puberty and improving mental health in TGD adolescents. However, key clinical and ethical considerations—such as bone health monitoring, fertility counseling, psychological support, and informed decision-making—must guide treatment. Long-term safety remains uncertain, particularly regarding skeletal health, reproductive outcomes and cancer risk. A precision medicine approach and co-produced longitudinal studies are essential to support safe, individualized care.Systematic review registrationhttps://www.crd.york.ac.uk, identifier CRD42024528334.